2014
DOI: 10.3171/2014.5.spine13570
|View full text |Cite
|
Sign up to set email alerts
|

Estimating EQ-5D values from the Neck Disability Index and numeric rating scales for neck and arm pain

Abstract: Object The Neck Disability Index (NDI) and numeric rating scales (0 to 10) for neck pain and arm pain are widely used cervical spine disease–specific measures. Recent studies have shown that there is a strong relationship between the SF-6D and the NDI such that using a simple linear regression allows for the estimation of an SF-6D value from the NDI alone. Due to ease of administration and scoring, the EQ-5D is increasingly being used as a measure of utility in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…According to prior studies, pain was shown to be the most common symptom of UF during pregnancy, and the risk of depression could increase in this situation [3, 8]. Some past studies used the EuroQoL Group’s five-dimension questionnaire (EQ-5D) to measure and assess the relationship between pain, depressive symptoms, and quality of life (QoL) [7, 9, 10]. Considering that most pregnant women do not have fatal diseases, it was suitable to use a generalized questionnaire to assess their HRQoL values.…”
Section: Introductionmentioning
confidence: 99%
“…According to prior studies, pain was shown to be the most common symptom of UF during pregnancy, and the risk of depression could increase in this situation [3, 8]. Some past studies used the EuroQoL Group’s five-dimension questionnaire (EQ-5D) to measure and assess the relationship between pain, depressive symptoms, and quality of life (QoL) [7, 9, 10]. Considering that most pregnant women do not have fatal diseases, it was suitable to use a generalized questionnaire to assess their HRQoL values.…”
Section: Introductionmentioning
confidence: 99%
“…No known studies have compared and mapped the individual items of NDI and SF-6D in patients with CNP, but a recent study by Carreon LY and colleagues compared the NDI with the EQ-5D-3 L in patients with neck and/or upper-extremity complaints [ 36 ]. They found no significant relationship between the EQ-5D-3 L and the NDI to allow for a valid estimation of EQ-5D-3 L indexes from the NDI using regression modeling, although the model using the individual NDI items had an R 2 of 0.46 and an RMSE of 0.172.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies of over 3,700 patients with degenerative cervical spine disorders and 14,500 patients with degenerative lumbar conditions undergoing surgical treatment, the authors could not accurately predict EQ-5D scores from Neck Disability Index, Oswestry Disability Index, or VAS scores. 23 24 For unclear reasons, however, when the same group performed similar studies using the SF-6D, they were able to develop models with a reasonable degree of accuracy. 25 26 …”
Section: Discussionmentioning
confidence: 99%